Research on a Robust Traceability Method for the Assembly Manufacturing Supply Chain Based on Blockchain - Cheng Li (Applied Sciences, 2025)
The management of assembly manufacturing supply chains in a cloud computing environment poses various challenges, including extensive regional management, a lack of transparency in the supply chain, an absence of a secure and effective traceability mechanism, and difficulties in achieving safe traceability. Therefore, this paper proposes a robust traceability scheme for assembly manufacturing supply chains based on blockchain technology. The solution utilizes IoT devices to collect data on product production and processing while ensuring the security and privacy of traceability information through digital signatures and hash encryption algorithms. Furthermore, by employing an “on-chain + off-chain” mixed storage strategy, the scheme achieves secure storage of traceable data. Additionally, the proposed scheme enhances the reliability of the traceability process through an efficient on-chain query mechanism and an off-chain trusted verification method. This research provides both theoretical foundations and technical pathways for enhancing the reliability of assembly manufacturing supply chains as well as their practical application.